TRIPLE BOTTOM LINE IN CULTURAL EVENTS: THE GENERATION-Z PERCEPTIONS - Sukmasari Triana Gita Putri; Wayan Gede Supartha; Putu Kemala Vidyantari (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This research examines indicators that are relevant to the Triple Bottom Line in Cultural Events based on the perceptions of Gen-Z. The phenomenon of the dominance of foreign cultures among Gen-Z society prompts the author to examine the sustainability of cultural events in Indonesia. This research was conducted using a purposive sampling approach and utilize factor analysis, with respondents being individuals born between 1995 and 2012, who were determined as Gen-Z, who have previously attended cultural events such as Bali Art Festival, Banyuwangi Ethno Carnival, Gandrung Sewu Festival, and others. Based on previous research, the triple bottom line (TBL) on cultural events has both positive and negative impacts. In this research, Gen-Z also agree that cultural events give benefits as well as some disadvantages for the local communities. They generally hold a very positive view regarding the social and economic contributions of cultural events, particularly in fostering community pride and boosting local economies. Gen-Z is concerned about potential negative impacts like littering and noise on the surrounding area. Overall, Gen-Z perceived the cultural events as promising events in the future. Still, they felt cultural events could not be a mediator for local product enhancement and environment cleanliness. It is hoped that this research could bring a contribution to further cultural festivals held by the organisers and governments in Indonesia.